Analysis of deformation characteristics of magnesium AZ80 wrought alloy under hot conditions - Kobold, Dominik (Strojniški vestnik, 2010)
Light-weight and environmentally friendly materials with good mechanical properties are much appreciated in various modern applications. Weight reduction can improve the performance of many components while reducing the fuel consumption of vehicles. Magnesium is one of the most popular weight-reducing materials because of its low density, good mechanical properties, large natural reserves and good machining properties. The strength, stiffness and favourable metallographic structure of products can beimproved by a forging process in which components are shaped from feedstock slugs by applying compressive force through various forging dies. However, widespread usage of forging technology in industrial practice is very rare in comparison to casting, due to the specific deformation characteristics of magnesium having a hexagonal close packed basal crystal structure. This paper deals with the determination of the influence of the most important process parameters on the deformation process of magnesium alloys. On the basis of extensive experimental study, anisotropic flow and the impact of the most important input process factors on the plastic deformation of AY80 wrought alloy are considered. The results presented in this paper are directly relatedto industrial practice and have significant potential as a case study for the further development of FEM models capable of predicting anisotropic material flow during applied plastic deformation. The studies presented in the paper also make possible defining recommended technological parameters of the forging process.
Keywords: kovanje; magnezij; magnezijeve zlitine; plastična deformacija; preoblikovanje kovin